Solar pumps and South Asia's energy-groundwater nexus: exploring implications and reimagining its future - Shah, Tushaar; Rajan, Abhishek; Rai, Gyan Prakash; Verma, Shilp; Durga, Neha (IOP Publishing, 2018)
South Asia's groundwater economy stands at the threshold of a revolution in adoption of solar irrigation pumps (SIPs). This has potential to unlock the region's perverse energy-groundwater nexus. In much of South Asia, the price of energy used in irrigation, the only surrogate for water price, fails to signal the abundance or scarcity of groundwater, resulting in myriad distortions. We analyse these in South Asia's eight distinct energy-groundwater interaction settings. We then explore SIP promotion policies to ease pressure on scarce groundwater in South Asia's 'groundwater depletion zone' and accelerate groundwater irrigation for poverty reduction in its 'groundwater abundance zone'.